Targeting hyaluronan metabolism-related molecules associated with resistant tumor-initiating cells potentiates chemotherapy efficacy in lung cancer - Díaz, Marco Aurelio (2024)
The success of chemotherapy regimens in patients with non-small cell lung cancer (NSCLC) could be restricted at least in part by cancer stem cells (CSC) niches within the tumor microenvironment (TME). CSC express CD133, CD44, CD47, and SOX2, among other markers and factors. Analysis of public data revealed that high expression of hyaluronan (HA), the main glycosaminoglycan of TME, correlated positively with CSC phenotype and decreased disease-free interval in NSCLC patients. We aimed to cross-validate these findings on human and murine lung cancer cells and observed that CD133 + CSC differentially expressed higher levels of HA, HAS3, ABCC5, SOX2, and CD47 (p < 0.01). We modulated HA expression with 4-methylumbelliferone (4Mu) and detected an increase in sensitivity to paclitaxel (Pa). We evaluated the effect of 4Mu + chemotherapy on survival, HA metabolism, and CSC profile. The combination of 4Mu with Pa reduced the clonogenic and tumor-forming ability of CSC. Pa-induced HAS3, ABCC5, SOX2, and CD47 expression was mitigated by 4Mu. Pa + 4Mu combination significantly reduced in vivo tumor growth, enhancing animal survival and restoring the CSC profile in the TME to basal levels. Our results suggest that HA is involved in lung CSC phenotype and chemosensitivity, and its modulation by 4Mu improves treatment efficacy to inhibit tumor progression.